Programmes for the management of preoperative anaemia: audit in ten European hospitals within the PaBloE (Patient Blood Management in Europe) Working Group. Issue 3 (26th December 2019) - Jung‐König, Mona; Füllenbach, Christoph; Murphy, Michael F.; Manzini, Paola; Laspina, Stefan; Pendry, Kate; Mühling, Jörg; Wikman, Agneta; Humbrecht, Catherine; Rigal, Jean‐Christophe; Lasocki, Sigismond; Folléa, Gilles; et al.
Abstract : Background and objectives: Preoperative anaemia is an independent risk factor for a higher morbidity and mortality, a longer hospitalization and increased perioperative transfusion rates. Managing preoperative anaemia is the first of three pillars of Patient Blood Management (PBM), a multidisciplinary concept to improve patient safety. While various studies provide medical information on (successful) anaemia treatment pathways, knowledge of organizational details of diagnosis and management of preoperative anaemia across Europe is scarce. Materials and methods: To gain information on various aspects of preoperative anaemia management including organization, financing, diagnostics and treatment, we conducted a survey (74 questions) in ten hospitals from seven European nations within the PaBloE (Patient Blood Management in Europe) working group covering the year 2016. Results: Organization and activity in the field of preoperative anaemia management were heterogeneous in the participating hospitals. Almost all hospitals had pathways for managing preoperative anaemia in place, however, only two nations had national guidelines. In six of the ten participating hospitals, preoperative anaemia management was organized by anaesthetists. Diagnostics and treatment focused on iron deficiency anaemia which, in most hospitals, was corrected with intravenous iron. Conclusion: Implementation and approaches of preoperative anaemia management vary across Europe with a primary focus on treating iron deficiency anaemia. Findings of this survey motivated the hospitals involved to critically evaluate their practice and may also help other hospitals interested in PBM to develop action plans for diagnosis and management of preoperative anaemia.